Edukasi Pencegahan Demam Berdarah Dengue (DBD) pada Anak Usia Sekolah di Sanggar Anak Sungai Deli, Medan Maimun - Muhammad Fakhry; Devi Nuraini Santi; Winni R.E. Tumanggor (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Dengue Hemorrhagic Fever (DHF) remains a major public health concern in tropical countries, particularly in densely populated communities with inadequate environmental sanitation. School-age children are considered a vulnerable group for dengue infection; however, they also possess significant potential to act as agents of change in promoting healthy and preventive behaviors within their families and communities. This Community Service Program (PKM) was designed to enhance children's knowledge and awareness regarding dengue prevention through engaging and age-appropriate health education. Method: The activity was conducted at Sanggar Anak Sungai Deli, Medan Maimun, involving 36 school-age participants. The intervention employed an experiential learning approach that combined interactive health education sessions with gamification-based activities, including educational coloring exercises and picture-guessing games related to dengue prevention. Program effectiveness was assessed using pre-test and post-test questionnaires to evaluate changes in participants’ knowledge levels. Result: The findings demonstrated substantial improvements across all assessed indicators. Understanding of dengue causes increased from 44.4% to 91.7%, knowledge of the dengue vector, Aedes aegypti, rose from 63.9% to 86.1%, and awareness of the 3M Plus preventive measures improved from 69.4% to 94.4%. Conclusion: These results indicate that integrating interactive educational strategies with gamified learning methods effectively strengthens children’s understanding of dengue prevention and encourages the development of preventive health behaviors from an early age.